Emerging trend in second messenger communication and myoendothelial feedback - Tran, Cam Ha T.; Kurjiaka, David T.; Welsh, Donald G. (Frontiers in Physiology, 2014)
Over the past decade, second messenger communication has emerged as one of the intriguing topics in the field of vasomotor control. Of particular interest has been the idea of second messenger flux from smooth muscle to endothelium initiating a feedback response that attenuates constriction. Mechanistic details of the precise signaling cascade have until recently remained elusive. In this perspective, we introduce readers to how myoendothelial gaps junctions could enable sufficient inositol trisphosphate flux to initiate endothelial Ca2+ events that activate Ca2+ sensitive K+ channels. The resulting hyperpolarizing current would in turn spreads back through the same myoendothelial gap junctions to moderate smooth muscle depolarization and constriction. In discussing this defined feedback mechanism, this brief manuscript will stress the importance of microdomains and of discrete cellular signaling.